2007
DOI: 10.1097/fjc.0b013e318059ae80
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol Inhibits Rat Aortic Vascular Smooth Muscle Cell Proliferation via Estrogen Receptor Dependent Nitric Oxide Production

Abstract: Vascular smooth muscle cell (VSMC) proliferation is pivotal in the progression of hypertension, atherosclerosis, and restenosis. Resveratrol is a grape polyphenol that is implicated as an important contributor to red wine's vascular protective effects. Its antimitogenic action on VSMC is attributed to an array of pleiotropic effects, including modulation of the estrogen receptor (ER). To elucidate the mechanisms underlying resveratrol-mediated ER modulation and its inhibition of VSMC proliferation, we treated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
39
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(41 citation statements)
references
References 55 publications
2
39
0
Order By: Relevance
“…Note that female animals were selected for these studies so as to maximize responses. However, 1) since male animals also express ERs in the vasculature (13,18), 2) since it is now recognized that ER-␣ contributes to physiological function in the male vasculature (9,27), and 3) since our prior studies in male compared with female vascular smooth muscle cells showed similar responses for Resv (14), we expect similar responses in male mice. In studies involving a pharmacological inhibition of NOS, the mice were administered N G -nitro-L-arginine methyl ester (L-NAME, 50 mg/kg) in their drinking water, starting 7 days before the denudation procedure, continuing through 14 days postdenudation.…”
Section: Animals Female Er-␣mentioning
confidence: 66%
See 3 more Smart Citations
“…Note that female animals were selected for these studies so as to maximize responses. However, 1) since male animals also express ERs in the vasculature (13,18), 2) since it is now recognized that ER-␣ contributes to physiological function in the male vasculature (9,27), and 3) since our prior studies in male compared with female vascular smooth muscle cells showed similar responses for Resv (14), we expect similar responses in male mice. In studies involving a pharmacological inhibition of NOS, the mice were administered N G -nitro-L-arginine methyl ester (L-NAME, 50 mg/kg) in their drinking water, starting 7 days before the denudation procedure, continuing through 14 days postdenudation.…”
Section: Animals Female Er-␣mentioning
confidence: 66%
“…In our prior work, we showed that Resv inhibited VSMC proliferation via an increase in NO production. These effects were abolished by a cotreatment with ER antagonist ICI-182780 (14). Recent studies also suggest that Resv binds ER-␣ and rapidly activates endothelial NOS (eNOS) nongenomically.…”
mentioning
confidence: 93%
See 2 more Smart Citations
“…[2][3][4] Epidemiological studies have also shown that red wine consumption was irreversibly correlated to a risk of coronary heart disease. 5) In practice, resveratrol inhibits the oxidation of human low-density lipoproteins, 6,7) platelet aggregation, 8) and the proliferation of vascular smooth muscle cells (VSMCs) [9][10][11][12][13][14] which can prevent the pathogenesis of atherosclerosis. Resveratrol is therefore believed to be a strong candidate for explaining the ''French paradox'' that indicates the reduction in coronary heart disease observed with red wine drinkers.…”
mentioning
confidence: 99%